Padrão de metadados no domínio museológico - Lima, Fábio Rogério Batista [UNESP]; Santos, Plácida Leopoldina V. A. C. [UNESP]; Segundo, José Eduardo Santarém [UNESP] (FapUNIFESP (SciELO), 2016)
It is in the Web environment that museums are making much of the information about their collection accessible in digital form. However, this information is being made available in an unstructured form. It hampers the exchange of data, communication and interoperability between museum systems that require suitable metadata standards to manage and provide information linked to their collections. The research question is: how can metadata standards contribute to art museums? The research presents a qualitative approach is theoretical character of descriptive and exploratory level. The result of the analysis showed that the metadata standards are not being used in Brazilian art museums, and there are not even national literature for dealing with this issue. However, in some countries is used some standards for the museological universe, of which the VRA Core version 4.0, which for cataloging works of art in the digital environment seems to be the most appropriate.
Standard metadata in museological domain
Keywords: Digital collection; Metadata standard for works of art; Museum in the Web environment; VRA Core